The effect of copper and cadmium on oxygen consumption of the juvenile common carp, Cyprinus carpio (L.) - Hassan, B.K. (Mesopotamian Journal of Marine Sciences, 2022)
This study was carried out on juvenile Cyprinus carpio (L.) to investigate the effects of sub-lethal concentrations of copper and cadmium (0.1, 0.25, 0.4 ppm) on the survival rate, oxygen consumption and histopathological changes in the gills of exposed fish. The results showed a decrease in survival rate with increasing concentration of each metal. Copper has the most toxic effect compared with cadmium, the survival rate has decreased from 50% to 10% for copper and from 70% to 20% for cadmium with increasing concentration for 15 days. The half lethal time (LT50) was (14 and >15) days for copper and cadmium, respectively. Oxygen consumption rate decreased with increasing concentration and there was a negative correlation between oxygen consumption and metal concentration. The exposure to each metal caused histopathological changes in the gill and resulted in separation of epithelial secondary gill lamellae, hyperplasia, fusion of secondary lamellae and necrosis.